Segmental Trisomy of Mouse Chromosome 17: Introducing an Alternative Model of Down's Syndrome. Issue 6 (2003) - Forejt, Jiri; Vacík, Tomáš; Gregorová, Soňa
Abstract : All of the mouse models of human trisomy 21 syndrome that have been studied so far are based on segmental trisomies, encompassing, to a varying extent, distal chromosome 16. Their comparison with one or more unrelated and non-overlapping segmental trisomies may help to distinguish the effects of specific triplicated genes from the phenotypes caused by less specific developmental instability mechanisms. In this paper, the Ts43H segmental trisomy of mouse chromosome 17 is presented as such an alternative model. The trisomy stretches over 32.5 Mb of proximal chromosome 17 and includes 486 genes. The triplicated interval carries seven blocks of synteny with five human chromosomes. The block syntenic to human chromosome 21 contains 20 genes.